2018
DOI: 10.7287/peerj.preprints.27036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemicals associated with plastic packaging: Inventory and hazards

Abstract: 23Global plastics production has reached 380 million metric tons in 2015, with around 40% used for 24 packaging. Plastic packaging is diverse and made of multiple polymers and numerous additives, along 25 with other components, such as adhesives or coatings. Further, packaging can contain residues from 26 substances used during manufacturing, such as solvents, along with non-intentionally added 27 substances (NIAS), such as impurities, oligomers, or degradation products. To characterize risks from 28 chemicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In fact, chemical exposure is the most rigorously studied human health impact of plastics. For example, humans are exposed through the additives and contaminants in plastic materials that come in contact with food (e.g., packaging, storage containers, utensils) (Groh et al 2018), children's toys (Guney and Zagury 2014), and electronics (Zeng et al 2016). There is some evidence that microplastics may act as vectors, transferring chemicals from the marine environment into organisms that are normally consumed by humans (Rochman et al 2014).…”
Section: Potential Effects Of Plastics On Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, chemical exposure is the most rigorously studied human health impact of plastics. For example, humans are exposed through the additives and contaminants in plastic materials that come in contact with food (e.g., packaging, storage containers, utensils) (Groh et al 2018), children's toys (Guney and Zagury 2014), and electronics (Zeng et al 2016). There is some evidence that microplastics may act as vectors, transferring chemicals from the marine environment into organisms that are normally consumed by humans (Rochman et al 2014).…”
Section: Potential Effects Of Plastics On Human Healthmentioning
confidence: 99%
“…The complexity of plastic materials makes recycling difficult. More specifically, a plastic product consists not only of the polymer itself, but also potentially thousands of chemical compounds, of which hundreds are known to be toxic (Groh et al 2018). These chemical additives can be problematic in recycling programs because they reduce the quality and safety of materials.…”
Section: Challenges Of Plastics Recyclingmentioning
confidence: 99%
“…Considering the chemical complexity of plastic consumer products, bisphenols and phthalates represent only the tip of the iceberg. A final article often consists of one or more polymers, multiple intentionally added substances, such as fillers or additives, as well as non-intentionally added substances, for instance residues from the manufacturing (13). Based on regulatory inventories, over 4000 substances are associated with plastic food packaging alone (13) and, overall, 10,547 chemicals are known to be used in plastics (14).…”
Section: Introductionmentioning
confidence: 99%
“…A final article often consists of one or more polymers, multiple intentionally added substances, such as fillers or additives, as well as non-intentionally added substances, for instance residues from the manufacturing (13). Based on regulatory inventories, over 4000 substances are associated with plastic food packaging alone (13) and, overall, 10,547 chemicals are known to be used in plastics (14). Moreover, empirical data suggests that plastics contain more chemicals than currently known.…”
Section: Introductionmentioning
confidence: 99%
“…[30] The use of devulcanized rubber (DR) in polymer blends could represent an interesting option for the valorization of rubber wastes. Considering that the worldwide plastics production has reached about 380 million tons in 2015, [31] the addition of a small percentage of DR in virgin matrices could imply a huge consumption of DR. [5] It will be, therefore, possible to produce materials with peculiar properties with respect to the pristine constituents, to substantially decrease the cost of the resulting compounds and to avoid the use of considerable amounts of raw materials. In literature, several examples can be found in which DR has been compounded with virgin rubber, and it was demonstrated that introduction of DR could strongly modify the processability and the mechanical performances of the resulting materials, with strong cost savings.…”
Section: Introductionmentioning
confidence: 99%